Synthesis and Biomedical Applications of Self-healing Hydrogels - Liu, Yi; Hsu, Shan-hui (Frontiers in Chemistry, 2018)
Hydrogels, which are crosslinked polymer networks with high water contents and rheological solid-like properties, are attractive materials for biomedical applications. Self-healing hydrogels are particularly interesting because of their abilities to repair the structural damages and recover the original functions, similar to the healing of organism tissues. In addition, self-healing hydrogels with shear-thinning properties can be potentially used as the vehicles for drug/cell delivery or the bioinks for 3D printing by reversible sol-gel transitions. Therefore, self-healing hydrogels as biomedical materials have received a rapidly growing attention in recent years. In this paper, synthesis methods and repair mechanisms of self-healing hydrogels are reviewed. The biomedical applications of self-healing hydrogels are also described, with a focus on the potential therapeutic applications verified through in vivo experiments. The trends indicate that self-healing hydrogels with automatically reversible crosslinks may be further designed and developed for more advanced biomedical applications in the future.